Matrix metalloproteinases in COVID-19: underlying significance. Issue 1 (1st March 2023) - Khalid, Usman; Dimov, Dimo; Vlaykova, Tatyana
Abstract: The role of matrix metalloproteinases (MMPs) in pathogenesis and severity of coronavirus disease 2019 (COVID-19) is under extensive exploration. MMPs are a family of extracellular proteases involved in a variety of physiological and pathological processes and conditions. The role of MMPs in COVID-19 stems from the pathogenesis resulting in the release of chemokines and pro-inflammatory markers which cause pulmonary oedema. In addition, the approaches to treatment of COVID-19 often are associated with some complications like acute lung injury due to extracellular matrix remodelling. In this respect, the aim of this review is to summarize, interpret and evaluate the significance of matrix metalloproteinases in SARS-CoV-2 infection in terms of the severity of the condition and delve into potential treatment from this perspective as well as highlighting the physiological and protective role of some MMPs.